2007
DOI: 10.1111/j.1365-2141.2006.06460.x
|View full text |Cite
|
Sign up to set email alerts
|

Matched sibling donor haematopoietic stem cell transplantation in Fanconi anaemia: an update of the Cincinnati Children's experience

Abstract: Summary Our results for 18 patients undergoing matched sibling donor stem cell transplant for Fanconi anaemia at Cincinnati Children's Hospital Medical Center were published in 1994. The present report updates our results in 35 consecutive patients. Thirty patients transplanted for marrow aplasia received cyclophosphamide 5 mg/kg for 4 d and 400 cGy thoraco‐abdominal irradiation. Five patients with clones involving chromosome 7, myelodysplastic syndrome or leukaemia received a more aggressive regimen with tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 29 publications
3
65
0
3
Order By: Relevance
“…While clinical studies in BM transplantation settings [4][5][6] suggest that normal HSC/progenitor cells could effectively engraft to FA BM under certain immunosuppressive conditioning, mechanistic studies on whether FA HSC/progenitor cells have cellautonomous defects in hematopoietic engraftment remain lacking. Previously, we and others have demonstrated that FA hematopoietic progenitor cells show poor engraftment in mouse knockout models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While clinical studies in BM transplantation settings [4][5][6] suggest that normal HSC/progenitor cells could effectively engraft to FA BM under certain immunosuppressive conditioning, mechanistic studies on whether FA HSC/progenitor cells have cellautonomous defects in hematopoietic engraftment remain lacking. Previously, we and others have demonstrated that FA hematopoietic progenitor cells show poor engraftment in mouse knockout models.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Allogeneic hematopoietic stem cell (HSC) transplantation from related and unrelated donors is the only known curative therapy for severe BM failure in patients with FA. 3,4 While outcomes from related donors seem to be good, 4 the use of unrelated donors as the HSC source has had limited success with poor survival due to graft rejection, graft-versus-host disease (GVHD), and treatment-related toxicities. The recent addition of fludarabine to the transplant preparative regimen for patients undergoing unrelated donor HSC transplantation has significantly reduced these problems, probably as a result of greatly enhanced immune suppression without overlapping toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…При этом показатели ОВ в данных исследованиях колебались от 83 до 88%, а смертность, связанная с ТГСК, -от 8 до 18,5 %. Отторжение транс-плантата зафиксировано в 8 % случаев, а РТПХ -в 12 % [23]. В одном из исследований была показана высокая доля острой РТПХ -36 % больных [24].…”
Section: режимы кондиционированияunclassified
“…11 Both types of conditioning regimens provided good results. As detailed in Table 1, [11][12][13] actuarial overall survival ranged between 83 and 88% with a TRM of 8-18.5%, highest failure rate of 8% and average chronic GVHD around 12%. Ac GvHD peaked to 36% in one study 12 and, along with TRM and chronic Ac GvHD, was remarkably high also in a small group of patients conditioned only with CY 80 mg/kg.…”
Section: Current Options For Treatment Of Marrow Failurementioning
confidence: 99%